WOMEN'S EMPOWERMENT THROUGH EDUCATION AND SKILLS TRAINING PROGRAMS - Navyandhini, Adela Marviola (LPPM Universitas Bina Bangsa, 2025)
Skills are one of the fundamental human needs to fulfill their life needs. One way that can be done is through entrepreneurship, especially for women. By entrepreneurship, women can not only increase family income, but also reduce dependence on men. The aim of this journal research is to analyze in depth the effectiveness of education and skills training programs in empowering women. This research aims to identify how these programs can increase women's capacity, provide wider access to economic opportunities, and encourage women's active participation in community development. The method used is a descriptive method with a literature approach, by analyzing 50 international and national journals that have been published online. Before the paper is published, it must first be discussed with peers and colleagues to get meaningful input. After the paper has been revised according to colleagues' input, the paper is published to increase the scope of scientific development. Based on the results of the literacy analysis, it can be concluded that entrepreneurship training can encourage women to become independent and improve their quality of life. This research can study how social, cultural and religious norms influence women's participation in skills training programs.